Optimization the Task of the National Narcotics Agency of South Sulawesi Province in the Control of Drug Abuse - Saleh, Abd. Rahman; Mas, Marwan; Hamid, Abd. Haris (Indonesian Journal of Legality of Law, 2018)
The purpose of this study was to determine the extent of drug control carried out by the National Narcotics Agency of South Sulawesi Province and the working relationship between the National Narcotics Agency of South Sulawesi Province and the Directorate of Narcotics in the South Sulawesi Regional Police. The data related to the task of the National Narcotics Agency of South Sulawesi Province in the Control of Drug Abuse are then analyzed using qualitative analysis, which describes the data that has been obtained and then concludes it. In the handling of drug abuse carried out by the National Narcotics Agency of South Sulawesi Province has been carried out as it should but in its implementation there are various kinds of obstacles or constraints and employment relationships of the National Narcotics Agency of South Sulawesi Province and the Directorate of Narcotics of the South Sulawesi Regional Police are regulated in 8 (eight) rooms scope and lack of coordination between the National Narcotics Agency of the Province of South Sulawesi and the Directorate of Narcotics Narcotics in South Sulawesi can lead to the emergence of sectoral ego that can make less optimal drug abuse control in the province of South Sulawesi